2023
DOI: 10.2147/ijwh.s364012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cardiovascular Risk in Women: Progress so Far and Progress to Come

Abstract: Cardiovascular disease is the leading cause of death in women worldwide. Nonetheless, there exist several uncertainties in the prediction, diagnosis, and treatment of cardiovascular disease in women. A cornerstone in the prediction of cardiovascular disease is the implementation of risk scores. A variety of pregnancy- and reproductive-factors have been associated with lower or higher risk of cardiovascular disease. Consequently, the question has been raised, whether these female-specific factors also provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…A recent systematic review investigated the addition of SS-RFs into current risk prediction tools and found the integration led to marginal, if any, improvements to risk prediction or classification. 47 Age at the time of assessment and the length of prediction time interval are possible confounders. Adding APO into the Framingham Risk Score yielded improvements in 15-year CVD prediction models but not in the established 10-year prediction.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review investigated the addition of SS-RFs into current risk prediction tools and found the integration led to marginal, if any, improvements to risk prediction or classification. 47 Age at the time of assessment and the length of prediction time interval are possible confounders. Adding APO into the Framingham Risk Score yielded improvements in 15-year CVD prediction models but not in the established 10-year prediction.…”
Section: Discussionmentioning
confidence: 99%